Endophthalmitis Caused by Bacillus cereus: Clinical Characteristics, Outcomes and Antibiotic Susceptibility - Jiayi Zheng; Liping Lin; Jingyu Liao; Xinlei Zhao; Jiaqi Lin; Fang Duan (MDPI AG, 2024)
Bacillus cereus endophthalmitis is a severe vision-threatening disease. This study aimed to analyze the clinical characteristics, antibiotic susceptibility, and risk factors for poor final visual acuity (VA) and enucleation or evisceration (ENEV) outcomes of B. cereus endophthalmitis patients. We retrospectively reviewed 52 cases (52 eyes) of culture-proven B. cereus endophthalmitis at Zhongshan Ophthalmic Center from January 2013 to December 2023. The mean age of the patients was 38.1 ± 20.1 years, and males composed the majority (90.4%) of the sample size; laborers (32.7%) and farmers (19.2%) were the primary occupations of the patients. All cases were caused by ocular trauma. Forty-one of 51 eyes (80.4%) had a final VA worse than the ability to count fingers (CFs), and 15 of the 52 total eyes (28.8%) underwent ENEV. Binary logistic forward (LR) regression analysis demonstrated that red eye (odds ratio [OR], 13.13; 95% confidence interval [CI], 1.58-108.80; p = 0.017), eye pain (OR, 22.87; 95% CI, 1.00-522.72; p = 0.050), and corneal edema/ulcer (OR, 13.13; 95% CI, 1.58-108.80; p = 0.017) were significant risk factors for poor VA outcomes. Conjunctival sac purulent discharge (OR, 10.08; 95% CI, 2.11-48.12, p = 0.004) and white blood cell (WBC) count (OR, 1.35; 95% CI, 1.06-1.72, p = 0.016) were significant risk factors for ENEV outcomes. B. cereus showed susceptibility rates of 100.0% to vancomycin and ofloxacin; 98.0% to levofloxacin; 93.3% to ciprofloxacin; 87.5% to imipenem; and 78.9% to tobramycin. The susceptibility to azithromycin and clindamycin was 66.7% and 50.0%, respectively. In contrast, B. cereus was resistant to penicillin (susceptibility at 3.8%), cefuroxime (5.6%), and cefoxitin (37.1%).